Education Personnel Satisfaction Index on UIN Walisongo Semarang Services - Pranatami, Dwimei Ayudewandari; Pranatami, Dwimei Ayudewandari; Umriana, Anila Umriana; Anggis, Eka Vasia (Journal of Quality Assurance in Islamic Education (JQAIE), 2021)
Quality assurance is one of the benchmarks that can be seen in assessing the quality of a university. All efforts that can be made related to the quality assurance process must be carried out starting from the level of study programs to tertiary institutions and a thorough evaluation not only related to the learning curriculum but also the human resources involved in it. One of the essential human resources involved in the learning process is educators. The optimal performance of educators will affect the whole teaching and learning process, and the implementation of these educators is strongly influenced by satisfaction with campus services. So, this study aims to analyze the satisfaction of education personnel with the services provided by the campus. Surveying educators carried out the data search process in the UIN Walisongo Semarang. Nine aspects are analyzed by the level of satisfaction by educators, namely 1) Recruitment and Selection, 2) Employee Orientation and Placement, 3) Training, Learning and Development Tasks, 4) Job Evaluation 5) Career Paths 6) Welfare 7) Attendance and Assignment System, 8) Termination and 9) Campus Facilities. The results of the analysis obtained are that the satisfaction of education personnel is at a moderate to a very high level with the aspect that shows the highest satisfaction in the achievement and assignment system variable (3.50) and the element that is at the lowest level of satisfaction is the welfare variable (3.14).